Thinking through and designing qualitative research studies: a focused mapping review of 30 years of qualitative research in sport psychology - Poucher, Z. A.; Tamminen, K. A.; Caron, J. G.; Sweet, S. N. (International Review of Sport and Exercise Psychology, 2020)
Amid the increasing use of qualitative methods in the field of sport psychology, a number of researchers have initiated discussions about issues of rigour and quality in qualitative inquiry. Methodological coherence has been offered as an approach to strengthening qualitative inquiry by ensuring that the elements of qualitative research are appropriately aligned. This study presents a focused mapping review and synthesis of the methodological coherence of qualitative sport psychology research published in five peer-reviewed journals over 30 years. 710 articles were subjected to an in-depth analysis. The philosophical position, methodology, data generation and analysis methods, presentation of findings, description of quality, statement of researcher position, and methodological coherence of each article were coded. Results indicated that post-positivist or critical realist approaches are dominant in sport psychology, although there has been an increase in the variety of philosophical positions employed over time. Further, the majority of articles in sport psychology were methodologically coherent. We conclude by forwarding practical considerations for thinking through and designing methodologically coherent qualitative studies in sport psychology, which are intended to be accessible for all researchers.